REFLEXÕES ACERCA DO IMPACTO DO CORONAVÍRUS SOBRE O DIREITO À SAÚDE E SUA TUTELA EM UMA PERSPECTIVA TRANSNACIONAL: REFLECTIONS ABOUT THE IMPACT OF CORONAVIRUS ON THE RIGHT TO HEALTH AND ITS PROTECTION IN A TRANSNATIONAL PERSPECTIVE (Revista Direito em Debate, 2021)
This text, developed under Inductive Method and from doctrinal and legislative research, brings some introductory reflections on the impact of the Coronavirus on the right to health and its protection in a transnational perspective. Initially, it briefly describes the Coronavirus, covering its characterization, origin and expansion. Then, it outlines the legal measures provided for Act n. 13.979, of February 6, 2020, for the Coronavirus confrontation in Brazil. Then, it goes on to examine the profiles of the tutelage of Public Health in Liberal, Social and Transnational State. Finally, it addresses some of the legal consequences of fighting Coronavirus.